Cyclomatic Complexity dan Graph Matrix dalam Pengujian Sistem Informasi Manajemen Rumah Sakit - Vikasari, Cahya (Infotekmesin, 2023)
Information systems can assist hospital management in improving services at a hospital. The software development method used in making hospital management applications is using the waterfall method which one of the stages is testing. The problem in system development is that the testing process is not optimal and focuses more on system development so that errors can be found at the implementation stage. System testing is a permit for an error in the system being developed. The aim of the research is to check the design details, use the program design control structure procedurally and run the program to find errors. The method applied to carry out the testing phase in the hospital management system is the Whitebox method using the cyclomatic complexity and graph matrix approaches. Testing will be carried out on the process of managing inpatient data in the application. The results of the research from testing the hospital management system using the cyclomatic complexity approach are that it can provide information on the minimum number of tests and ensure that all program structure paths are used at least once. In addition, the results of the graph matrix test are the probability side that will be carried out.